KEPUTUSAN PEMBELIAN E COMMERCE SHOPEE - Dynanda Amelyea Cantika Putri (2020)
This research aims to analyse and find out whether there is an influence between sales promotion, word of mouth, and e service quality toward consumer buying decisions. The method that used in this research is descriptive quantitative with 100 respondents of e commerce Shopee consumer which is spread in Jakarta Selatan. The data analysis system used is through quesionnare with descriptive and inferential analysis techniques using Smart PLS 3.2. Results of this research showed that sales promotion and e service quality are positively influence consumer buying decisions. In contrast, word of mouth has no influence toward consumer buying decisions.